12. New Telemedicine protocol and patented remote-EEG system from Terni S. Maria Hospital Neurophysiology Division: Experimental assessment and pathway towards large scale service. Issue 12 (December 2017) - Stipa, G.; Gabbrielli, F.; Frondizi, D.; Colosimo, C.; Caproni, S.; Fanelli, C.; Gobbi, D.; Giorgi, L.; Mancini, A.; Domiziani, M.; Pasqui, R.; Carletti, S.
Abstract : Terni S. Maria Hospital Neurophysiology Division successfully performed experimental trial for innovative Telemedicine service, using patented remote-EEG system. The Neurophysiologist can be connected from everywhere to the hospital information system through virtual private network and remote device. EEG-passive electrode device is effectively controlled by different direct Remote Desktop freeware softwares. EEG-diagnosis is possible at distance avoiding file exchanges and fulfilling privacy and safety criteria. The connection shares the graphic interface from EEG device desktop to the remote Neurophysiologist, who can also directly control EEG device functions. From 2009 to 2017 a total of 261 EEGs (standard and continuous monitoring) were examined. In the first 6 years, specialists operated on EEG device at distance but they sent medical reports by telefax, while from 2016 to 2017 they used report files with digital signature. Two hospital deliberations (n. 875 dated 2008/12/29 and n. 198 dated 2015/03/18) validated the procedure for clinical use, even if into the research protocol. These trial-evidences as well the new regulations on Telemedicine (Intesa Stato-Regioni n. 123/CSR 2016/7/7; EU Directive 2011/24; EU Regulation 2016/679) pave the way for large scale usage of this protocol. The Group of study on Telemedicine in Neurophysiology founded by SINC and Digital-SIT works on this purpose.